PERFORMANCE OF BITUMEN BOUND MASONRYBLOCK INCORPORATING WASTE MATERIALS - Arya Thanaya, I Nyoman (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 1 Januari 2010, 2012)
Continuous efforts are needed in utilizing waste materials in building industry. This investigation was intended to use waste materials, namely: steel slag, crushed glass and coal fly ash for producing Masonryblock, i.e. a masonry building block bound with bitumen (asphalt). The binder used was bitumen of 50 pen. The materials were pre-heated at 160 °C for 3 hours before mixing and compacted using static compactor at 8 MPa. The properties of the blocks evaluated were compressive strength and creep. In order to minimize creep deformation, the samples were heat cured at 160 °C for 24, 48, and 72 hours. Creep test was carried out by loading the samples using a cantilever arm loading equipment with 1 MPa stress until the creep strain stable. The strain was measured by means of a 50 mm Demec gauge. It was found that the Masonryblock compressive strength comparable to the concrete block commonly used in the United Kingdom (UK). The sample requires at least 48 hours curing in order to satisfy creep performance requirement.
Keywords: masonry, waste materials, steel slag, crushed glass, fly ash.